2012
DOI: 10.1177/0091270010394851
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Pegylated Liposomal CKD‐602 (S‐CKD602) in Patients With Advanced Malignancies

Abstract: S-CKD602 is a pegylated long-circulating liposomal formulation of CKD-602, a potent topoisomerase I inhibitor. A population pharmacokinetic (PK) model for encapsulated and released CKD-602 following administration of S-CKD602 was developed to assess factors that may influence S-CKD602 PK. Plasma samples from 45 patients with solid tumors were collected in a phase 1 study. S-CKD602 was administered as a 1-hour intravenous infusion with doses ranging from 0.1 to 2.5 mg/m(2) . Plasma concentrations of encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…She was the only patient enrolled on our study with detectable tumors in her liver. Thus, the higher MPS activity and CL of PLD in this patient may be explained in part by the reported relationship between tumor metastases in liver and the CL of NP (Wu et al, 2011). Our group has previously reported that patients with primary or metastatic tumors in their liver (n 5 21) had a significantly (P 5 0.02) higher CL of the NP S-CKD602 compared with individuals without tumors in their liver (n 5 8) (22).…”
Section: Discussionmentioning
confidence: 60%
“…She was the only patient enrolled on our study with detectable tumors in her liver. Thus, the higher MPS activity and CL of PLD in this patient may be explained in part by the reported relationship between tumor metastases in liver and the CL of NP (Wu et al, 2011). Our group has previously reported that patients with primary or metastatic tumors in their liver (n 5 21) had a significantly (P 5 0.02) higher CL of the NP S-CKD602 compared with individuals without tumors in their liver (n 5 8) (22).…”
Section: Discussionmentioning
confidence: 60%
“…Linear and nonlinear PK models were constructed for encapsulated CKD-602, and it was determined that liver tumor was a significant covariate for maximum velocity. Including liver tumor as a covariate in the model decreased the variation in Vmax by 29% [70]. The inter-patient variability in S-CKD602 PK disposition could possibly be explained by the presence of metastatic liver tumors, as the Vmax of patients with these tumors is 1.5-fold higher than those patients without liver tumors [70].…”
Section: Presence Of Liver Tumorsmentioning
confidence: 99%
“…In a Phase I PK study evaluating encapsulated and released CKD-602, 45 patients were enrolled, of which 26 individuals had tumor(s) of all types in their liver [70]. Linear and nonlinear PK models were constructed for encapsulated CKD-602, and it was determined that liver tumor was a significant covariate for maximum velocity.…”
Section: Presence Of Liver Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…102 PEG-bearing liposomes are not opsonized or affected by complement components, and consequently evade capture by mononuclear phagocytic system cells. 103,104 Finally, the presence of PEG in liposome formulations prevents aggregation, favors the formation of small, monodisperse particles, and increases the EPR effect, due to the extended circulation time and escape from the RES. 105 The practical consequences of these phenomena are evident when the biopharmaceutical profiles of Stealth liposomes and conventional liposomes are contemplated.…”
Section: Liposomes In Nanomedicinementioning
confidence: 99%